Left atrial function assessed by real-time 3-dimensional echocardiography is related to right ventricular systolic pressure in chronic mitral regurgitation - Saraiva, Roberto M. (2009)
Roberto M. Saraiva. Fundação Oswaldo Cruz. Instituto Nacional de Infectologia Evandro Chagas. Documento produzido em parceria ou por autor vinculado à Fiocruz, mas não consta a informação no documento.